Hepatitis C treatment program in Maputo, Mozambique, the challenge of genotypes and key populations: A 5‐year retrospective analysis of routine programmatic data. Issue 4 (30th March 2023) - Loarec, Anne; Gutierrez, Ana Gabriela; Muvale, Gil; Couto, Aleny; Nguyen, Aude; Yerly, Sabine; Pinto, Yolanda; Madeira, Natercia; Gonzales, Alan; Molfino, Lucas; Ciglenecki, Iza; Antabak, Natalia Tamayo
Abstract: Background and Aims: Hepatitis C (HCV) programs face challenges, especially linked to key populations to achieve World Health Organization (WHO) goals of eliminating hepatitis. Médecins Sans Frontières and Mozambique's Ministry of Health first implemented HCV treatment in Maputo, in 2016 and harm reduction activities in 2017. Methods: We retrospectively analyzed routine data of patients enrolled between December 2016 and July 2021. Genotyping was systematically requested up to 2018 and subsequently in cases of treatment failure. Sustainable virological response was assessed 12 weeks after the end of treatment by sofosbuvir‐daclatasvir or sofosbuvir‐velpatasvir. Results: Two hundred and two patients were enrolled, with 159 (78.71%) males (median age: 41 years [interquartile range (IQR): 37.10, 47.00]). Risk factors included drug use (142/202; 70.29%). One hundred and eleven genotyping results indicated genotype 1 predominant (87/111; 78.37%). Sixteen patients presented genotype 4, with various subtypes. The people who used drugs and HIV coinfected patients were found more likely to present a genotype 1. Intention‐to‐treat analysis showed 68.99% (89/129) cure rate among the patients initiated and per‐protocol analysis, 88.12% (89/101) cure rate. Nineteen patients received treatment integrated with opioid substitution therapy, with a 100% cure rate versus 59.37% (38/64) for initiated ones without substitution therapy ( p < 0.001). Among the resistance testing performed, NS5A resistance‐associated substitutions were found in seven patients among the nine tested patients and NS5B ones in one patient. Conclusion: We found varied genotypes, including some identified as difficult‐to‐treat subtypes. People who used drugs were more likely to present genotype 1. In addition, opioid substitution therapy was key for these patients to achieve cure. Access to second‐generation direct‐acting antivirals (DAAs) and integration of HCV care with harm reduction are crucial to program effectiveness.